2008
DOI: 10.1258/ijsa.2007.007259
|View full text |Cite
|
Sign up to set email alerts
|

Linear array genotyping and hybrid capture II assay in detecting human papillomavirus genotypes in women referred for colposcopy due to abnormal Papanicolaou smear

Abstract: The main objective of this study was to assess the feasibility of human papillomavirus (HPV) genotyping in women referred for colposcopy due to abnormal Papanicolaou (Pap) smear. A series of 248 women referred for colposcopy due to an abnormal Pap smear were analysed with the Roche Linear Array HPV genotyping test detecting 37 most frequent HPV types, and compared with hybrid capture II (HCII) assay for oncogenic (high-risk [HR] HPV) types as well as for p16INK4a expression using immunocytochemistry. All tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 47 publications
2
11
0
Order By: Relevance
“…The advantages and disadvantages of these two basically different methodologies have been extensively discussed [719]. …”
Section: Introductionmentioning
confidence: 99%
“…The advantages and disadvantages of these two basically different methodologies have been extensively discussed [719]. …”
Section: Introductionmentioning
confidence: 99%
“…The pooled absolute specificity for excluding CIN2 + and CIN3 + was 45% (95% CI, 41%‐50%) and 42% (95% CI, 34%‐51%), respectively (Table and Fig. ) . The corresponding SROC plots for the outcomes of CIN2 + and CIN3+, shown in Figure , display the variation of the test accuracy in the individual studies as well as the overall pooled accuracy.…”
Section: Resultsmentioning
confidence: 95%
“…Nineteen studies reported accuracy data for the HC2 assay (Digene Corp, Gaithersburg, Md) . Four studies reported accuracy data for other hrHPV DNA testing; they included 2 using Linear Array HPV genotyping (Roche Molecular Diagnostics, Almeda, Calif), 1 using the Cervista HPV HR test (Hologic, Marlborough, Mass), and 1 using multiplex polymerase chain reaction with genotype‐specific primers (Eurofins MWG Operon, Huntsville, Ala) . For 2 studies, accuracy data were obtained for HPV‐16/18 genotyping .…”
Section: Resultsmentioning
confidence: 99%
“…This test detects the presence of HR-HPV and does distinguish the genotype present. The Linear Array genotyping test is a reverse line blot assay for detection and genotyping of 37 types of HPV [Lenselink et al, 2008;Monsonego et al, 2008;Iftner et al, 2009]. The LA test is the standard for assessment of new HPV genotyping tests [Meijer et al, 2006;Liu et al, 2009;Mariani et al, 2010;Koshiol et al, 2013;Lan et al, 2013].…”
Section: Introductionmentioning
confidence: 99%